The principle of uberrimae fidei in insurance contracts: Analysis of health insurance contracts and their legal implications on persons living with HIV/AIDS in Tanzania - Kanje, Aden Adolf (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Master of Laws (LL.M) Degree of Mzumbe University